Multi‐trophic impacts of an invasive aquatic plant. (November 2016) - Kuehne, Lauren M.; Olden, Julian D.; Rubenson, Erika S.
Summary: Natural resource agencies are increasingly required to prioritise management of multiple non‐native aquatic plants (macrophytes) in freshwater ecosystems. Characterising the consequences of invasions for ecological processes and corresponding ecosystem services is fundamental to this decision‐making process, but requires an understanding of impacts across physical, chemical, and biological responses. Accordingly, we evaluated the multi‐trophic impacts of the invasive macrophyte Myriophyllum aquaticum (Haloragaceae; parrotfeather) along the mainstem Chehalis River, Washington, U.S.A. We examined invertebrate, plant and fish community responses to varying degrees of parrotfeather abundance and simultaneously characterised variation in physical structure and dissolved oxygen (DO) across the dominant native and non‐native plant species. DO concentrations were significantly reduced and approached hypoxic levels in areas dominated by parrotfeather compared with native vegetation. Increased structural complexity, volume and biomass of parrotfeather was associated with increased diversity of epiphytic invertebrates. However, these more diverse invertebrate assemblages were dominated by amphipods, whereas native macrophytes were characterised by cladocerans, chironomids and gastropods. Non‐native fishes (primarily centrarchid species) were more strongly associated with sites where parrotfeather was present and diversity of non‐native fishes was positively correlated along a gradient of parrotfeather abundance. Native fish associated with parrotfeather areas were those that tend to be tolerant of degraded or lower quality habitats. We saw little evidence of exclusion of other macrophytes; native and non‐native plant diversity and abundance were positively correlated with the parrotfeather gradient. This may reflect that analysis was done at a site level, and competitive dominance might be apparent by changes in species richness at smaller (plot) scales or over longer periods. Alternatively, parrotfeather may demonstrate minimal effects on native plant composition. Given the effects observed across multiple habitat characteristics and biota, parrotfeather appears to be a highly impactful invader where it establishes. Many of the changes we observed appear to derive from the emergent leaves and dense mat formation of parrotfeather compared with a submersed structure more typical of the native community. Our results suggest that managers should specifically consider contrasting characteristics between non‐native and native physical structure when assessing and prioritising threats of invasive macrophytes.